Distanciados, pero conectados: importancia del vínculo pedagógico en la enseñanza remota por emergencia - Fernández Godenzi, Adriana Isabel (2023)
This research aims to analyze the shifts produced in the pedagogical relationship within the emergency remote teaching (ERT) implemented as a result of the COVID-19 pandemic, specifically to describe the forms of interaction within the teaching-learning process that students have had with their teachers, as well as with their peers. For this purpose, virtual group interviews were conducted with 12 Peruvian university students. The selection of interview participants was intentional and by convenience. As outcomes, it has been found that the forced passage to virtuality has generated absences, distances and distrust that have affected their teaching-learning processes; it has also allowed the emergence of empathy and the possibility of methodological innovation in the virtual classroom. Finally, it can be concluded that for the students the inter-subjective pedagogical bond with their teachers and among themselves is crucial to generate and sustain meaningful learning processes.